2020
DOI: 10.2147/ndt.s266136
|View full text |Cite
|
Sign up to set email alerts
|

<p>CPCGI Reduces Gray and White Matter Injury by Upregulating Nrf2 Signaling and Suppressing Calpain Overactivation in a Rat Model of Controlled Cortical Impact</p>

Abstract: Background: Compound porcine cerebroside and ganglioside injection (CPCGI), which involves injection of a neurotrophic drug, has been widely used to treat certain brain disorders in the clinic; however, the detailed mechanism is unknown. This study investigated whether CPCGI protects the brain from trauma by stimulating antioxidative nuclear factor erythroid-2-related factor 2 (Nrf2) signaling and suppressing calpain overactivation in a rat model of controlled cortical impact (CCI). Materials and Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…11,12 A previous study revealed that CPCGI exerts protective effects against TBI by upregulating the Nrf2 signaling pathway, lessening oxidative stress and suppressing the overactivation of calpain. 13 This study primarily investigated whether CPCGI protects the brain against TBI through repressing both mitochondrial apoptotic and PARP/NF-κB inflammatory signaling after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 A previous study revealed that CPCGI exerts protective effects against TBI by upregulating the Nrf2 signaling pathway, lessening oxidative stress and suppressing the overactivation of calpain. 13 This study primarily investigated whether CPCGI protects the brain against TBI through repressing both mitochondrial apoptotic and PARP/NF-κB inflammatory signaling after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…found that GM1, the active ingredient of CPCGI, inhibited in ammation and activation of NF-κB signaling pathway, respectively. Meanwhile, a recent study proved that CPCGI could reduce cortical neuronal apoptosis by inhibiting NF-κB signaling pathway in traumatic brain injury [35]. Conversely, we concluded that CPCGI attenuates hippocampal in ammation and thus reduces neuronal apoptosis by inhibiting the phosphorylation expression level of NF-κB signaling pathway.…”
Section: Declarations Ethics Approvalmentioning
confidence: 67%